Water network optimisation with consideration of network complexity - Ong, B.; Pang, Y.; Wan, J.; Yap, A.; Ng, Wendy; Foo, D. (The Italian Association of Chemical Engineering, 2015)
This paper presents a superstructural model for the synthesis of water network, with the objective to reduce its complexity. A less complex network will ease its operation. Different constraints are added to the model, i.e. reduced piping length and number of piping connections. Literature case study comprises of ten water-using processes is used to demonstrate the approach.